The Role Of Ambidextrous Leadership Moderates The Effect Of Supply Chain Network Risk Drivers On Financial Performance - Arya Irawan Putra Palguna; Bahtiar Usman; Henny Setyo Lestari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to examine the influence of supply chain network risk drivers on supply chain exploration and exploitation practices and their implications for financial performance. This research uses a quantitative approach with descriptive and verification methods. The observational units consisted of 92 executives from manufacturing companies listed on the Indonesia Stock Exchange. The findings reveal that supply chain network risk negatively impacts exploration and exploitation practices, with implications for company financial performance. Exploitation has a positive and significant impact on financial performance, whereas exploration does not exhibit a significant effect. Although the direct effect of network risk on financial performance is insignificant, ambidextrous leadership has been shown to positively and significantly moderate this relationship. The managerial implication of this study is that strengthening exploitation practices is key to maintaining financial performance when facing supply chain risks. Ambidextrous leadership plays a crucial role in transforming the impact of risks into opportunities by emphasizing the need for adaptive leadership in uncertain situations. This research is original in its study of the moderating role of ambidextrous leadership in the risk-performance relationship, a study that is still limited in operations management and supply chain studies.   Keywords: Supply Chain Network Risk Drivers, Supply Chain Exploration & Exploitation practices, Ambidextrous Leadership and Firm Financial Performance.